1985
DOI: 10.4319/lo.1985.30.4.0794
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and photosynthetic action spectra for natural phytoplankton populations: Implications for production in the open ocean1

Abstract: The hypothesis that variation in the initial slope of the photosyiithesis-irradiance curve due to variations in wavelengths of light could be responsible for lower rar es of estimated photosynthesis in the open ocean is tested by direct measurement of photosynthetic action spectra (12-X bands, 25-nm bandpass, eight intensities per band) for natural populatio 1s from the well mixed waters containing the spring plankton bloom in the Sargasso Sea. We conclude that this possibility is unlikely, at least at this ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 43 publications
(46 reference statements)
3
42
0
1
Order By: Relevance
“…As shown in expenments by Lewis et al (1985), a' vanes significantly with wavelength due to its linear correlation with the particulate absorption spectrum of phytoplankton. Uncorrected ADP calculations were 59 to 108% of corrected values when based on a' values which ignored the in viv0 underwater light spectrum (Table 4a).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in expenments by Lewis et al (1985), a' vanes significantly with wavelength due to its linear correlation with the particulate absorption spectrum of phytoplankton. Uncorrected ADP calculations were 59 to 108% of corrected values when based on a' values which ignored the in viv0 underwater light spectrum (Table 4a).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The spectral dependent parameter a' from samples taken at depth z was corrected to approximate maximum light utilisation coefficient i n situ according to the relationship in Lewis et al (1985):…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the extent to which variations in a,,*@) contribute to variations in estimates of primary production is unknown. Lewis et al (1985) showed that the initial slope of the P vs. Z curve (a") has the largest potential impact, in terms of error, on estimates of areal primary production, @ being the product of the maximal quantum yield of photosynthesis (4,) and the mean specific absorption coefficient weighted by the spectrum of the scalar irradiance between 400 and 700 nm (a"* in the present study, t%c in some others).…”
mentioning
confidence: 98%
“…Details of these sensors, including Lewis et al (1985) compared the effect of errors in their estimated precision and accuracy, are described the determination of P$ and cu on estimates of depthin Denman et al (1985). integrated photosynthesis derived from these parameSamples were taken from the depth within the upper ters.…”
Section: Introductionmentioning
confidence: 99%